Merit, Meaning, and Human Bondage : An Essay on Free Will - Arpaly, Nomy (Book collections on Project MUSE., 2006)
Perhaps everything we think, feel, and do is determined, and humans--like stones or clouds--are slaves to the laws of nature. Would that be a terrible state? Philosophers who take the incompatibilist position think so, arguing that a deterministic world would be one without moral responsibility and perhaps without true love, meaningful art, and real rationality. But compatibilists and semicompatibilists argue that determinism need not worry us. As long as our actions stem, in an appropriate way, from us, or respond in some way to reasons, our actions are meaningful and can be judged on their m.